Late Pleistocene paleoenvironment of southern China: Clay mineralogical and geochemical analyses from Luna Cave, Guangxi, China. (20th October 2020) - Huang, Shengmin; Hong, Hanlie; Liao, Wei; Wang, Chaowen; Cheng, Liuling; Hao, Xiudong; Li, Dawei; Bae, Christopher J.; Wang, Wei
Abstract: A number of important early Late Pleistocene human fossils have been found in southern China. These new data have contributed to a major revision of the traditional Out of Africa model that argues modern humans did not disperse out of Africa until after 60 ka. At the same time, these findings have attracted increased attention by paleoclimate specialists (e.g., vertebrate paleontologists, sedimentologists) interested in identifying the characteristics and understanding the living environment of the region in which these early Late Pleistocene modern humans lived in. Unfortunately, research focused on the reconstruction of the Late Pleistocene paleoenvironment in southern China is still very limited. Here, we present an analysis of the clay mineral assemblage and geochemical characteristics of the sedimentary deposits from Luna Cave, one of these important early Late Pleistocene modern human sites in southern China. The results from the sedimentological analyses are consistent with previous paleontological and geological studies that showed the paleoclimate was strongly influenced by the East Asian monsoon and that the Late Pleistocene environment was relatively stable warm and humid. Further studies of coeval sites from the region are necessary to determine whether this is a consistent pattern across southern China or specific to the Bubing Basin.